Thin MAPb0.5Sn0.5I3 Perovskite Single Crystals for Sensitive Infrared Light Detection - Wu, Jinming; Zhang, Yongqiang; Yang, Shuang; Chen, Zhaolai; Zhu, Wei (Frontiers in Chemistry, 2022)
Metal halide perovskite single-crystal detectors have attracted increasing attention due to the advantages of low noise, high sensitivity and fast response. However, the narrow photoresponse range of widely-investigated lead-based perovskite single crystals limit their application in near infrared (NIR) detection. In this work, Tin (Sn) is incorporated into methylammonium lead iodide (MAPbI3) single crystals to extend the absorption range to around 950 nm. Through space-confined strategy, MAPb0.5Sn0.5I3 single crystal thin films with thickness of 15 μm is obtained, which is applied for sensitive NIR detection. The as-fabricated detectors show responsivity of 0.514 A/W and specific detectivity of 1.4974×1011 cmHz1/2/W under 905 nm light illumination and zero bias. Moreover, the NIR detectors exhibit good operational stability (~30000s), which can be attributed to the low trap density and good stability of perovskite single crystals. This work demonstrates an effective way for sensitive NIR detection.